THE IMPORTANCE OF LINGUACULTURAL KNOWLEDGE IN THE PROCESS OF TRANSLATION - Yakubov Zafar Kudratovich (Scholar Express Journals, 2025)
Translation is not merely a linguistic exercise but an intricate process that requires deep understanding of the cultural context behind the language. Linguacultural knowledge—the awareness of the interconnectedness of language and culture—plays a pivotal role in ensuring accurate, meaningful, and culturally appropriate translations. This article explores the significance of linguacultural competence in translation, reviews relevant literature, analyzes practical examples of translation challenges, and discusses implications for translator training. The study concludes that effective translation depends heavily on the translator’s ability to navigate cultural nuances alongside linguistic accuracy.
Keywords: Linguacultural knowledge; translation; culture